Theorem 4: ∼P ⇒ (P ⇒ Q)
We begin the proof using the same steps as in the previous theorems, using the construction rule to decompose the implications in the goal.
Now we use the new concepts from negation. We have hypothetical evidence for both P and ¬P, but ¬P can be unfolded to mean (P ⇒ False). So if we use the application rule to apply (P ⇒ False) to P we get an assumption of False. By the False elimination rule, from False anything follows, including Q.
- View the proof in PDF format
- Step through the proof in the frame:
Table of Contents